(3Ndb GdEfSGfs - (3YHO Gdedc Hf bQjH Hf Ydj Hf CUeY GdHGgdj, CHh SYjO GdCUeYj,J (B216 (3g` s
(3ChdgG (B:s
(3bGd CHh SYjO YHO Gdedc Hf bQjH GdCUeYi GdHGgdi (B: (3jbGd ddeQCI ai Chd eG JMed (B: (3bO fSFJ aEPG GTJgJ , Ydi MedgG TjFkG , agi hMei Ydi RfI ScQi , hGdeUOQ GdhMe s
(3BNQgG (B:s
(3hai GdQLd (B: (3GdYQL hGdbRd YQL jYQL YQLkG EPG MOK Hg YQL , hYQL jYQL YQLkG (B: (3EPG eTi eTjJg GdYQLGf s
(3HgG BKGQ QWhHI hfbY eGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B162 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B187s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GddZIs